Ritual Kalili Pada Masyarakat Desa Mokobeau Kecamatan Siompu Barat Kabupaten Buton Selatan - Wilda, Wilda; koodoh, Erens E. (JURNAL KABANTI: Kerabat Antropologi, 2025)
Traditional ceremonies can be a characteristic of a society because they are the result of the culture created by that society. This research aims to find out and describe the reasons why the Kalili ritual is still maintained and the process of implementing the Kalili ritual. This research uses a qualitative description method with an ethnographic approach. The results of the research show that the Mokobeau Community still maintains the Kalili ritual to this day. This ritual aims to facilitate the fortunes of married couples, speed up the birth of offspring, and ensure that their children will not fall ill easily in the future. The process of carrying out the Kalili ritual is that the husband carries a toddler belonging to someone else and is male, then followed by ten women who are married and have carried out the Kalili. The Kalili participants will walk around the house seven times, namely to the right four times and to the left three times. The process of going around the house is led by a bhisa. After that, the Kalili participants will go up to the house and continue several ritual processions, namely kabanti carried out by Bhisa, handing over the child to the wife, blowing out candles, fighting over ketupat, and katuturai. The meaning of this procession is that the husband and wife will quickly have children, and the good fortune they get will continue to be distributed.